Characteristic Control of SWCNT-FET by Varying Its Chirality and Dimensions - Zahraa Eisa; Haider Al-Mumen (IAES Indonesian Section, 2022)
Carbon nanotube (CNT) has witnessed great importance due to its electronic and mechanical properties. The CNTFET was designed to provide high-performance electronic devices. Therefore, the carbon nanotube is representing a potential material for future microelectronic devices. In this paper, COMSOL Multiphysics was used to design and a simulate single-walled carbon nanotube field-effect transistor with a back gate. The insulation layer used in the model was silicon dioxide. The influence of changing its thickness on the drain current was discussed. In addition, the specification of carbon nanotubes was investigated in terms of changing their diameter and length. Moreover, this paper reveals the current transport of CNTFET for different applied gate voltage and drain voltage. In our work, the CNTFET behaves as n-type FET with transconductance gm≈1.25uA and electron mobility equal to 4.77×10-26cm2v-1s-1. To obtain semiconducting properties for the CNT material, it must consider the chirality when altering the carbon nanotubes diameter. In the proposed device, the diameter values range from 1nm to 4.5nm. It was found that increasing the diameter range resulted in decreasing bandgap from 0.497 eV to 0.110 eV and increasing drain current from 4.075 uA to 31.33 uA.